Effects of tibiofemoral mobilization in patients of Patellofemoral pain syndrome - Ishrat Fatimah; Saira Waqqar (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the effects of tibiofemoral joint mobilization on pain and Range of motion in patient with patellofemoral pain syndrome. Methods: This randomized control trial was conducted at Lady Reading Hospital and Hayatabad Medical Complex in Peshawar from July 2019 to August 2019. Total 52 participants of both gender were selected, who met inclusion criteria of age 25 to 35 years, anterior knee pain of at least one month. They were randomly allocated through sealed envelope method. Control group received specific 6 exercises of hip and knee with conventional treatment while experimental group received PFJ mobilization prior to same exercises advised to control group. Numeric pain rating scale, Kujala Anterior Knee Pain Scale, Algometer and Goniometer were outcomes measuring tools used to take measurements at baseline and after every 3rd session i.e. 3 sessions per week in 4 weeks. Results: This study stated that Experimental group showed more improvement in pain on Numerical Pain Rating Scale, ROM, Pressure Pain Threshold (PPT) and Type of Pain. According to Kujala Anterior knee pain score Experimental group indicated significant improvement in daily activities i.e. limping, weight bearing, walking, squatting, stairs climbing, squatting, running and jumping. Conclusion: This study concluded that TFJ mobilizations prior to hip and knee exercises were more effective in terms of ROM, Type of pain and pressure pain threshold than exercises of hip and knee joint Clinical Trial Number: Identifier: NCT04225000 Continuous...